Structural and optical properties of the lead-free zero-dimensional hybrid perovskites (NH4)2SnCl6 and [(CH3)2NH2]4InCl7 - Stascxak Neto, Vasco (2023)
Hybrid perovskites are gaining attention from the scientific community because of their applications in optoelectronics, data storage and solar cells. In this work we synthesized the perovskite-like hybrid halides (NH4)2SnCl6 and [(CH3)2NH2]4InCl7 DMA4InCl7 by using the slow evaporation method. Using X-ray diffraction, we were able to determine their crystalline structures belonging to the space groups cubic Fm-3m and orthorhombic P21212, respectively, which are maintained at low temperatures. In order to analyze their structural properties, we performed Raman spectroscopy at low temperatures in both compounds and, from these measurements, we analyzed the ammonium reorientation dynamics in the compound (NH4)2SnCl6 and, for DMA4InCl7 we analyzed the emission peak behavior as a function of temperature, which allowed us to attribute this emission peak to the presence of self-trapped excitons.